Cognitive changes in post- COVID-19 (Research, Society and Development, 2022)
This study seeks to evaluate changes in memory, attention and related cognitive functions in patients who were severely affected by COVID-19 in Campina Grande, Paraíba. The research had a descriptive and exploratory character, being of quantitative nature. It was carried out from the application of two instruments: The Prospective and Retrospective Memory Questionnaire (PRMQ-10) in its version translated for Portuguese, and the Rey Complex Figure Test (FCR). The variables were analyzed using the Statistical Package for the Social Sciences (SPSS) – version 20.0. The research had 30 participants, 17 men (56.7%) and 19 women (43.3%), with a mean age of 52±14 years. The mean score of the PRMQ-10 was 12.2±1.3, while the copy and memory steps of the FCR scored an average of 29.1±8.6 and 18±1.6, respectively. The proportion of success of the memory step in relation to the respective copy step had an average of 60%±3.9%. The results suggest a significantly lower than expected cognitive performance of executive functions, memory and attention. It is imperative to expand the scope of these studies through other research approaches and with a more diverse sample. We suggest the making of longitudinal studies, which can more accurately analyze the effects of COVID-19 on cognition, based on the individual's own history.